Buprenorphine poisoning in children: a 10‐year‐experience of Marseille Poison Center. (28th November 2019) - von Fabeck, Katharina; Boulamery, Audrey; Glaizal, Mathieu; de Haro, Luc; Simon, Nicolas
Abstract: Buprenorphine is a µ‐partial agonist and k‐antagonist acting on central opioid receptors. Patented for analgesia in 1968, buprenorphine has been used as opioid substitutive therapy since the 1990s, as well as methadone. The aim was to document pediatric poisoning, to discover the severity, and to evaluate the treatment with naloxone. All pediatric poisonings reported to the poison control center Marseille (France)—from January 1, 2009 to December 31, 2018—were included. Analysis put value on gender, age, estimated quantity, symptoms and their delay, place of treatment, medical treatment, utilization of antidotes, severity of intoxications, and patients' outcome. Fifty‐four infant poisonings with buprenorphine were recorded, doses varied between 1 and 36 mg, and children showed mainly neurological (somnolence, miosis…) and gastroenteric (vomiting) effects. Pulmonary effects were described for four children. According to the poisoning severity score, 8 intoxications were classified as 'no symptoms or signs', 37 as minor poisonings, 3 as moderate, none as severe or fatal and 6 were unknown. Medical care was required for 46 children, and four of them were treated with naloxone. Buprenorphine poisoning can cause neurological, gastroenteric, and respiratory symptoms. Even licking a tablet leads to intoxication because of maximal tablet's absorption while placing it under the tongue. Hospital admission is necessary even at small doses. Naloxone was efficient in the four described cases. Parents have to be aware of the poisoning risk with buprenorphine. Recently, commercialized instantly dissolving formulations could cause more severe intoxications.